Multiscale numerical modeling of solid particle penetration and hydrocarbons removal in a catalytic stripper. Issue 9 (19th July 2021) - Woo, Mino; Giannopoulos, George; Rahman, Md Mostafizur; Swanson, Jacob; Stettler, Marc E. J.; Boies, Adam M.
Abstract: The catalytic stripper has emerged as a technology for removal of semivolatile material from aerosol streams for automotive and aerospace emissions measurements, including portable solid particle emissions measurements governed by the Real Driving Emissions regulations. This study employs coupled energy and mass transfer models to predict solid particle penetration and hydrocarbon removal for various configurations of a catalytic stripper. The continuum-scale macromodel applies mass, momentum and energy conservation for the inlet heating region of a catalytic stripper whereby the catalyst monolith is represented by a porous medium. The particle and species dynamics inside the catalytic monolith were computed by coupled microsimulations of the monolith channel using boundary conditions from the macromodel. The results from the numerical simulations were validated with corresponding experimental data and employed using a parametric study of flow rate and catalyst length with a view to optimizing the operating condition. Results of the simulation and experiment show that solid particle penetration through the catalytic stripper can exceed approximately 60% for particles at 10 nm mobility diameter and hydrocarbons removal of >95% for an optimized catalytic stripper device.